Buku Tamu Digital Menggunakan Teknologi Optical Character Recognition Dan Framework Laravel - Rapar, Pedro Vincensius; Rorimpandey, Gladly Caren; Tinambunan, Medi Hermanto (Program Studi Teknik Informatika, 2025)
The use of information technology has become essential in improving operational efficiency and data accuracy, particularly in visitor registration systems. At PT. Pertamina Geothermal Energy Area Lahendong, visitor data collection was still carried out manually, often resulting in long queues, unreadable handwriting, and data management difficulties. This study proposes the development of a web-based digital guest book system using Optical Character Recognition (OCR) technology and the Laravel framework. OCR is employed to extract visitor data automatically from images of ID cards (KTP), eliminating the need for manual entry. The system was developed using the Rapid Application Development (RAD) methodology, which emphasizes iterative prototyping and user involvement. User Acceptance Testing (UAT) showed a high satisfaction score of 90.2%, categorized as